Improving the Photoconductivity of a Fullerene-Based Oligomer with Polythiophenes - Simõis, André V.S. [UNESP]; Borro, Marcelo S. [UNESP]; Riga, Luiz A. [UNESP]; Medina, Maria Eduarda R.S. [UNESP]; Ferreira, Nyara D. [UNESP]; Maximino, Mateus D. [UNESP]; Ramanitra, Hasina H.; Hiorns, Roger C.; Olivati, Clarissa A. [UNESP] (FapUNIFESP (SciELO), 2024)
Organic solar cells offer significant advantages over traditional inorganic solar cells, including their lightweight nature, ease of fabrication, low cost, and low energy investment. Recent advances have shown that oligo and poly(fullerene)s play an important role in both types of devices, either as additives or interlayers, significantly improving stability and charge extraction. There is considerable room for further progress in understanding the properties of these novel materials. Here, we examine OPCBMMB, an oligo(fullerene) based on PCBM, and study its changes in photoconductivity when combined with thiophenes. The OPCBMMB:P3HT and OPCBMMB:P3OT composites are formed from drop casting, with optical and electronic characterizations being performed. UV characterizations confirm a difference in macromolecular conformation of the P3HT and P3OT going from solution to film, as would be expected. More interesting is the great improvement in the films conductivities when studied under direct current when compared to pristine OPCBMMB. Differences arise due to the variations in thiophene alkyl chains. The combination of OPCBMMB:P3HT and OPCBMMB:P3OT also proved to be an effective combination of acceptor-donor, with a visible increase in conductivity when exposed to light. A fact that can be correlated to the UV spectra, which shows the blends have a strong interaction with visible light.
Keywords: Fullerene-Based; Oligomers; Photoconductivity; Polythiophenes